Multi-media based workout assistance for obese adolescents / Hanis Syakirah Roslan, Nur Hasni Nasrudin and Rosida Ahmad Junid - Roslan, Hanis Syakirah; Nasrudin, Nur Hasni; Ahmad Junid, Rosida (Universiti Teknologi MARA, Perak, 2023)
With the increasing prevalence of obesity among teenagers, it becomes crucial to promote their health and fitness. This paper presents an innovative approach that utilizes multi-media and augmented reality (AR) technology to enhance physical activity and combat the issue of adolescent obesity. The proposed method involves creating an interactive fitness environment through a smartphone application that seamlessly integrates AR elements. This software offers guidance to overweight adolescents during their workouts to ensure they maintain proper form. To keep users motivated and engaged, interactive content like videos and visuals has been incorporated. The objectives of the study involve the identification of functionalities within fitness apps aimed at helping overweight teenagers exercise more efficiently. It also entails the creation and deployment of a multimedia prototype application, along with the evaluation of user satisfaction on the system usages. The methodology involves several key stages, including requirement gathering, application design and development, and conducting assessments based on the Technology Acceptance Model (TAM). The evaluation results have demonstrated the potential of AR-enhanced training applications to combat adolescent obesity. This study showcases the potential of AR-enhanced training application as a promising path for improving health and well-being.